Aging brain (Elsevier, 2021)
"Aging Brain is an Open Access journal that complements Neurobiology of Aging which, in its 40th anniversary in 2020, is the premier journal in the field of aging neuroscience. Aging Brain will publish papers that contribute to knowledge of the mechanisms underlying healthy (or adaptive) and pathological aging of the brain, as well as the iterative communication of signals between the brain, other organs and the external environment that promote or disrupt the mental health span. Papers that employ multiple levels of analysis, that integrate knowledge from established and emerging disciplines and technological developments, and which demonstrate translation into improved medical approaches, are particularly welcome."--Publisher.
Keywords: Brain : Diseases : Age factors : Periodicals; Central nervous system : Aging : Periodicals; Neurobiology : Periodicals; Aging : Periodicals; Neurophysiology : Periodicals; Older people : Periodicals; Aging; Brain : physiology; Neurophysiology; Cerveau : Maladies : Facteurs liés à l'âge : Périodiques; Système nerveux central : Vieillissement : Périodiques; Neurobiologie : Périodiques; Vieillissement; Personnes âgées; Neurophysiologie; elderly; Brain : Diseases : Age factors; Central nervous system : Aging; Neurobiology